(untitled) (Altre Modernità, 2012)
Milan’s Guides from the second half of XIX century don’t seem to be very interested in linguistic history of the town and its current usage, evolving from the dialect to the adoption of the national language. Two remarkable exceptions are the short treatises dues to Cesare Cantù from one side and Carlo Salvioni from the other.